دور الإحالة النصية في اتساق قصيدة (من هنا) لأحمد سحنون - عبابة, البشير (جامعة الوادي - university of Eloued, 2021)
يتناول هذا البحث موضوعا من موضوعات لسانيات النص يتمثّل في الإحالة؛ إذ تسهم في اتساق النص بصفة عامة بما فيه الخطاب الشعريّ الذي جسّدته قصيدة (من هنا) لأحمد سحنون, وتبيين دور الإحالة النصية في تماسك هذا الخطاب المقصود بالبحث الذي يتكون من العديد من الأبيات التي تعلّق بعضها ببعض شكلا ومعنى من خلال استعمال أدوات عديدة من بينها وسائل الإحالة المختلفة؛ إذ تعدّ وسيلة لربط العناصر المتباعدة بشكل يقتصد في النص ويجنّبه التكرار ما يجعله بنية نصية مترابطة ومتماسكة . Abstract: This study has dealt with one of the topics of text-linguistics which is reference, as it contributes to the cohesion of the text in general, including the poetic discourse embodied in the poem (Min Houna/ From Here) of Ahmed SAHNOUN. This study also has shown the role of textual reference in the coherence of this discourse intended by the research that consists of many verses that are connected with each other in form and meaning through the use of many tools, including the different tools of reference. These reference tools are considered a way to link the divergent elements in a way that economizes the text and avoids repetition. This makes it a coherent and cohesive textual structure.
مقال
Keywords: إحالة؛ اتساق؛ إشارة؛ ربط؛ ضمير; reference; cohesion; sign; link; pronoun